Surface-Associated Plasminogen Binding of Cryptococcus neoformans Promotes Extracellular Matrix Invasion - Stie, Jamal (Public Library of Science, 2009)
BACKGROUND: The fungal pathogen Cryptococcus neoformans is a leading cause of illness and death in persons with predisposing factors, including: malignancies, solid organ transplants, and corticosteroid use. C. neoformans is ubiquitous in the environment and enters into the lungs via inhalation, where it can disseminate through the bloodstream and penetrate the central nervous system (CNS), resulting in a difficult to treat and often-fatal infection of the brain, called meningoencephalitis. Plasminogen is a highly abundant protein found in the plasma component of blood and is necessary for the degradation of fibrin, collagen, and other structural components of tissues. This fibrinolytic system is utilized by cancer cells during metastasis and several pathogenic species of bacteria have been found to manipulate the host plasminogen system to facilitate invasion of tissues during infection by modifying the activation of this process through the binding of plasminogen at their surface. METHODOLOGY: The invasion of the brain and the central nervous system by penetration of the protective blood-brain barrier is a prerequisite to the establishment of meningoencephalitis by the opportunistic fungal pathogen C. neoformans. In this study, we examined the ability of C. neoformans to subvert the host plasminogen system to facilitate tissue barrier invasion. Through a combination of biochemical, cell biology, and proteomic approaches, we have shown that C. neoformans utilizes the host plasminogen system to cross tissue barriers, providing support for the hypothesis that plasminogen-binding may contribute to the invasion of the blood-brain barrier by penetration of the brain endothelial cells and underlying matrix. In addition, we have identified the cell wall-associated proteins that serve as plasminogen receptors and characterized both the plasminogen-binding and plasmin-activation potential for this significant human pathogen. CONCLUSIONS: The results of this study provide evidence for the cooperative role of multiple virulence determinants in C. neoformans pathogenesis and suggest new avenues for the development of anti-infective agents in the prevention of fungal tissue invasion.